Towards a new court management?. (2nd January 2018) - Jeuland, Emmanuel
Abstract : Court management may be defined as the administration inside the court and outside the case. It is inside the courts, so court management does not concern the general administration of justice. It is outside the cases, so court management does not deal with the administration of cases, the so-called case management. Yet, these three fields belong to the same category of judicial management or judicial administration, and there is some overlapping and even confusion. As a matter of fact, the concept of court management is not completely settled. In a descriptive approach, it can be said that court management deals with leadership inside a court, the relationship between the judges and court staff, the allocation of cases, the evaluation of judges and court staff, the court budget, the real estate, the maintenance and security of the building, the new technology, human resources and judicial communication. Court management deals with the different councils and assemblies of the court as well as with specific planning. This General Report is based on fifteen national reports (outside China). The approach to court management may vary according to the organization, the tradition and the location of the country studied (for example, the role of the public prosecutor in court management may vary). Court management is becoming a common concern everywhere in the world as part of the efforts to avoid backlogs, unreasonable duration of proceedings and costly litigation. It seems that the tasks of management are more and more given to a specialized clerk (the director of clerks or court manager) while the role of leadership remains in the hands of the head of the court who is usually a judge. The management we are considering is a new management based on indicators, objectives and evaluations coming from the new public management. Could it be possible that the common law is more at ease with new management than the civil law? Since the judge is appointed at a certain mature age, usually forty-five in common law countries, and sometimes with the legitimacy of election, there is no risk of competition between court leadership and court management, and so between court management and procedural law. Conversely, in civil law countries judges are considered as civil servants and are chosen at a much younger age, around twenty-three, and without electoral legitimacy. As a result, there is a risk of competition between court manager (director of clerks) and judges. After the executive model based on hierarchy and the management model based on indicators and evaluation, this paper suggests that a third model of court administration is possible: the relational model based on coordination. The principle of cooperation between judges, parties and lawyers applies to case management and procedural law in general. It could be said that the principle of coordination is the equivalent of the principle of cooperation in the field of court management. One result of this is the formation of court committees and the holding of regular meetings so that staff, judges, citizen and lawyers can improve together the functioning of the court.